2004
DOI: 10.1007/s00208-004-0529-y
|View full text |Cite
|
Sign up to set email alerts
|

Construction of some families of 2-dimensional crystalline representations

Abstract: We construct explicitly some analytic families ofétale (ϕ, Γ)-modules, which give rise to analytic families of 2-dimensional crystalline representations. As an application of our constructions, we verify some conjectures of Breuil on the reduction modulo p of those representations, and extend some results (of Deligne, Edixhoven, Fontaine and Serre) on the representations arising from modular forms.Résumé. -Nous construisons explicitement des familles analytiques de (ϕ, Γ)-moduleś etales, qui donnent lieuà des … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(132 citation statements)
references
References 14 publications
6
124
0
2
Order By: Relevance
“…Condition (5) has been verified by Berger [5] (improving on earlier results of various authors [7,9,10,15]). We now turn to condition (7).…”
Section: Lemma Let V Be An Irreducible Trianguline Representation Lsupporting
confidence: 70%
“…Condition (5) has been verified by Berger [5] (improving on earlier results of various authors [7,9,10,15]). We now turn to condition (7).…”
Section: Lemma Let V Be An Irreducible Trianguline Representation Lsupporting
confidence: 70%
“…A few years ago this question seemed to be regarded as almost intractible for weights k > p: as far as we know, the only results for high weights were those of Berger, Li and Zhu ( [BLZ04]) who showed that for v(a p ) sufficiently large (an explicit bound depending on k) the answer was the same as for the case a p = 0 (which was already known). Not only that, computational evidence collected by one of us (KB) seemed to indicate that the answer to the question was in general rather subtle.…”
mentioning
confidence: 98%
“…Theorem 4.1 (2)(i) for weights k ≤ p − 1 is proven in [18]. The weight k = p + 1 case is proved in [38] when the lift is non-ordinary at p: note that then residually the representation is irreducible at p of Serre weight 2 by results of Berger-Li-Zhu [8]. Alsoρ does arise from a newform of level prime to p and weight p + 1 by the weight part of Serre's conjecture together with multiplication by the Hasse invariant (see 12.4 of [26]), or Corollary 1 of Section 2 of [21], using Lemma 2 of [13] to avoid the hypothesis N > 4 in [21].…”
Section: → Omentioning
confidence: 96%
“…We have the following lemma which uses easy extensions of results in [22] and [7] (for (i)) and [8] (see prop. 6.1.1. for (iii)).…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation